The potential of nature's unseen industrious heroes: marine viruses. (12th April 2022) - Allen, Michael J.; Cicéron, Félix; Monier, Adam
Abstract : The last two years have been a crash course in educating the world about viruses, virology and infectious diseases. Unsurprisingly, viruses have emerged as the harbingers of doom. However, with their newly acquired knowledge, the new armchair virologists fail to grasp the importance of viruses in the living world. They may cause us harm, but without their relentless activity, we'd all be dead anyway. In addition to owing them our lives, they also have the potential to improve our lives with novel biotechnological applications.